The Effect of Students Motivation Towards Reading Skill at 10th Grade of SMK Nusantara Beber-Cirebon; A Survey Study - Utami Rosalina; Dwi Nopiyadi; Virga Putra Darma (Ilmu Inovasi Nusantara, 2022)
Motivation is an important factor in learning English. Students who have motivation will give more attention to learning. This research was to find out the students’ motivation toward reading skills. Data were obtained by questionnaire and test. The writer distributes the questionnaire to 60 students in the 10th grade of SMK NUSANTARA Beber-Cirebon. Instruments of validity and reliability are carried out by SPSS 25.0 for Windows. The writer made a hypothesis to answer the research problem. This research revealed that the tobservedis more than ttable (11.806> 2.00172).The probability value (p) is also less than 0.05 (p= 0.000 < 0.05). It can be proved with the result of the hypothesis testing, which is tobserved is more than ttable. The probability value (p) is also fewer than0.05 (p= 0.000 < 0.05). The finding of this research helps the English teacher of SMK NUSANTARA Beber-Cirebon to decide on the right teaching strategies to teach English. Therefore, it can maintain students’ motivation and improve students’ reading skills and achievement in learning English